Epigenetic Alterations and MicroRNA Misexpression in Cancer and Autoimmune Diseases: a Critical Review - Saito, Yoshimasa; Saito, Hidetsugu; Liang, Gangning; Friedman, Jeffrey M. (Clinical reviews in allergy & immunology, 2014)
Epigenetic markers such as DNA methylation and histone modifications around promoter regions modify chromatin structure and regulate expression of downstream genes. In fact, aberrant epigenetic modifications are common events in human disease including tumorigenesis and autoimmunity. Small non-coding RNAs named microRNAs (miRNAs) are modulators of gene expression and play critical roles in various cellular processes. Several miRNAs have been characterized as tumor suppressors or oncogenes in cancer, and recent reports implicate certain miRNAs in the pathogenesis of autoimmune diseases. Epigenetic investigations have shown that distinct miRNAs are directly regulated by DNA methylation and histone modifications at their promoters. Moreover, miRNAs themselves are key participants in regulating the chromatin modifying machinery. Chromatin-modifying drugs such as DNA methylation inhibitors and histone deacetylase inhibitors have shown efficacy in human malignancies and there is some evidence that these drugs may be useful in autoimmune disease. The benefits of these drugs are at least partially mediated by restoring expression of epigenetically silenced tumor suppressor genes, including miRNAs. The complex layers regulating gene expression have yet to be fully elucidated, but it is clear that epigenetic alterations and miRNA misexpression are essential events in pathologic processes, especially cancer and autoimmune disease, and represent promising therapeutic targets.